The Transformation of Religious Values in the Digital Life of Adolescents - Komala, Imas; Khairiyah, Ayu; Tombi Layuk Tulak, Jeremi; Azainil, Azainil (Advances In Social Humanities Research, 2024)
The transformation of religious values in the digital era has become an interesting phenomenon, especially for teenagers who are actively using technology. This study aims to analyze how religious values are internalized, modified, and applied in the digital lives of adolescents. With a qualitative approach, data is collected through in-depth interviews, observations, and literature studies. The results of the study show that adolescents use digital platforms to learn religion, such as taking online studies, reading religious articles, and discussing in online forums. However, there are challenges in the form of the dissemination of invalid information and the negative influence of social media on religiosity consistency. This study emphasizes the importance of guidance from families, educational institutions, and religious leaders in shaping healthy media consumption patterns and supporting the internalization of religious values.